Analysis of surface quality and optimization of process parameters in laser-assisted cutting of SiC ceramics. (1st September 2022) - Dai, Di; Zhao, Yugang; Cao, Chen; Liu, Qian; Liu, Guangxin; Song, Zhuang; Zhang, Xiajunyu; Zheng, Zhilong; Zhang, Haiyun; Dong, Ruichun
Abstract: In order to improve the surface quality of laser-assisted turning silicon carbide (SiC) ceramics, the effects of laser power, rotational speed, cutting depth and feed speed on surface quality are investigated. Taking the surface roughness as the characterization value, the reasonable selection range of each factor is determined by the numerical simulation results of temperature field and the single factor experiment results; orthogonal experiments and range analysis are performed on laser power, rotational speed, cutting depth and feed speed, the primary and secondary order of influence on surface roughness and the optimal combination of process parameters are obtained. The surface topography of the cutting area was observed by 3D digital microscope and the surface roughness is calculated. Taking surface roughness as the evaluation index, the reasonable selection range of each factor is obtained through temperature field simulation and single factor experiment results analysis as follows: laser power 230 ∼ 245 W, rotational speed 1500 ∼ 1650 r min −1, cutting depth 0.1 ∼ 0.2 mm, and feed speed 2 ∼ 4 mm min −1 . Through orthogonal experiment and range analysis, the order of the significant degree of the influence of various process parameters on surface roughness and the optimal combination of process parameters are obtained. The order of the significant degree of the influence of various process parameters on surface roughness Ra is as follows: laser power (P) > cutting depth (ap ) > feed speed (f) > rotational speed (n); the optimal combination of process parameters is as follows: laser power 235 W, rotational speed 1620 r min −1, cutting depth 0.1 mm and feed speed 2 mm min −1 . Compared with the surface quality of original workpiece, the surface of the SiC workpiece processed under the optimal combination of process parameters has no cracks and damage marks, and the surface roughness is reduced to 0.293 μ m, which significantly improves the surface quality of the SiC workpiece.